Soil and water conservation in ravinous watersheds - Bhan, Suraj; Arora, Sanjay (Indian Farming, 2020)
Reclamation of ravine lands has started since many decades where most of the activities are based on Integrated Farming System approach on watershed basis. In some of the projects, it resulted in cumulative gain in terms of area reclaimed, people benefited and knowledge gained which can be fruitfully utilized for future ravine reclamation planning. However, still efforts for the reclamation of ravine land needs to be adopted for productive use of these lands. The reclamation should aim for improvement of socioeconomic conditions of ravine areas apart from providing sustainable livelihood to the people of the area. The region has potential for diversified crops including highly remunerative medicinal and aromatic crops. Introduction of these crops calls for an integrated bio-industrial approach for locally processing the produce that would provide additional income to farmers and generate employment.